BASIC PILLARS OF INTEGRATED TRANSPORT SYSTEM (Perner's Contacts, 2009)
In this paper are presented basics of full functional and integrated transport system - conditions of carriage, tariff conditions and service conditions.
Keywords: integrated transport systems; passenger transport; condition of carriage; tariff conditions; service conditions